2019
DOI: 10.1097/scs.0000000000005619
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Concepts of Primary Dynamic Facial Nerve Reconstruction in the Oncologic Patient

Abstract: Transection of the facial nerve and its branches during extensive ablative procedures in the oncologic patient causes loss of control of facial mimetic muscles with severe functional and aesthetic sequelae. In such patients with advanced tumorous disease, copious comorbidities, and poor prognosis, rehabilitation of the facial nerve has long been considered of secondary priority. However, recent advances in primary facial nerve reconstruction after extensive resection demonstrated encouraging results focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The transfer is suggested as part of a triple facial nerve reanimation (defined above), to maximize axon supply to the face and avoid synkinesis. Nerve transfer is an attractive treatment option here, not only because the single coaptation and use of a vascularized nerve are important factors in an area designated for radiation therapy (Klein et al, 2019 ), but also because of the shorter reinnervation time following a more distal direct innervation, which can be crucial in patients with potentially poor prognosis. In these cases, the ACN is a clear choice for direct MMN reconstruction because of the easy nerve access in the already generous surgical field, together with the aforementioned benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transfer is suggested as part of a triple facial nerve reanimation (defined above), to maximize axon supply to the face and avoid synkinesis. Nerve transfer is an attractive treatment option here, not only because the single coaptation and use of a vascularized nerve are important factors in an area designated for radiation therapy (Klein et al, 2019 ), but also because of the shorter reinnervation time following a more distal direct innervation, which can be crucial in patients with potentially poor prognosis. In these cases, the ACN is a clear choice for direct MMN reconstruction because of the easy nerve access in the already generous surgical field, together with the aforementioned benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with facial nerve resection from ablative oncological procedures are traditionally regarded as poor candidates for facial nerve reanimation. This is often attributed to advanced age, presence of multiple comorbidities, adjuvant radiotherapy, and poor survival prognosis (Klein et al, 2019 ). However, recent studies have shown that neither age (Hembd et al, 2018 ) nor post‐operative radiation therapy (Gidley et al, 2010 ) preclude good and consistent reanimation outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Vascularized nerve grafts have several benefits when compared to their nonvascularized counterparts, including an increase in the number of myelin fibers, thickness, axon diameter, faster axonal regeneration, and higher axonal count. 18 Vascularized grafts are not always feasible to retrieve. However, when the patient requires soft tissue reconstruction of a level II injury, the vastus lateralis motor nerve can be harvested with the vascularized pedicle of the lateral femoral circumflex descending branch (►Fig.…”
Section: Other Available Optionsmentioning
confidence: 99%
“…A vastus lateralis motor branch graft provides minimal donor morbidity due to its multiple branches and sufficient length for grafting in a level II injury zone of the facial nerve. 18 Level II Case A 28-year-old male presents with a mammary analogue secretory carcinoma in the left parotid gland. He underwent parotidectomy with sacrifice of the left facial nerve with reconstruction (►Fig.…”
Section: Other Available Optionsmentioning
confidence: 99%